Pengembangan Modul Pedoman Guru dalam Mendesain Instrumen Penilaian Matematika Berbasis Pemecahan Masalah Matematika - Antok Kurniawan; M Rusdi; Jefri Marzal (Edumatika : Jurnal Riset Pendidikan Matematika, 2019)
This study aims to determine the process, specifications, and teacher's perception of developing a teacher guidance module in making mathematical assessment instruments based on mathematical problem-solving. This study uses the Research and Development method which is used to produce certain products, namely teacher guidance modules. The development model used in this study is the development model that Marshall et al. (2009), Tryon and Bishop et al (2012) and Rusdi (2018) combined by researchers into references. The steps consist of the problem and need analysis, literature review, product design, validity, practitioner trials. The research subjects in this development were two validators consisting of material expert validators, instrument design expert test validators, and five practitioners. The type of data taken in this study is qualitative data. The instrument used in the study was an open questionnaire. The process stages in developing are (a) Analysis of problems and needs, (b) literature review, (c) product design, (d) validity, (e) trial practitioners. The product specifications developed in the module are that there are three chapters on introduction, concepts, and procedures accompanied by examples by using types of problem-solving, namely problem-solving design and story problem. Teacher's perception in the teacher guidance module is positive, of the five practitioners recommending that it be used as a guide in making problem-solving problems.